At nonzero temperatures, stacked structures of methylated nucleic acid base pairs and microhydrated nonmethylated nucleic acid base pairs are favored over planar hydrogen-bonded structures: a molecular dynamics simulations study - Kabelác, M; Hobza, P (Chemistry (Weinheim an der Bergstrasse, Germany), 2001)
The dynamic structure of all ten possible nucleic acid (NA) base pairs and methylated NA base pairs hydrated by a small number of water molecules (from 1 to 16) was determined by using molecular dynamics simulations in the NVE microcanonical and NVT canonical ensembles with the Cornell force field (W. D. Cornell, P. Cieplak, C. I. Bayly, I. R. Gould, K. M. Merz, D. M. Ferguson, D. C. Spellmeyer, T. Fox, J. E. Caldwell, P. Kollman, J. Am. Chem. Soc. 1995, 117, 5179). The presence of one water molecule does not affect the structure of any hydrogen-bonded (H-bonded) nonmethylated base pair. An equal population of H-bonded and stacked structures of adenine...adenine, adenine...guanine and adenine... thymine pairs is reached if as few as two water molecules are present, while obtaining equal populations of these structures in the case of adenine...cytosine, cytosine...thymine, guanine... guanine and guanine...thymine required the presence of four water molecules, and in the case of guanine...cytosine, six. A comparable population of planar, H-bonded and stacked structures for cytosine...cytosine and thymine... thymine base pairs was only obtained if at least eight water molecules hydrated a pair. Methylation of bases changed the situation dramatically and stacked structures were favoured over H-bonded ones even in the absence of water molecules in most cases. Only in the case of methyl cytosine...methyl cytosine, methyl guanine...methyl guanine and methyl guanine...methyl cytosine pairs were two, two or six water molecules, respectively, needed in order to obtain a comparable population of planar, H-bonded and stacked structures. We believe that these results give clear evidence that the preferred stacked structure of NA base pairs in the microhydrated environment, and also apparently in a regular solvent, is due to the hydrophilic interaction of a small number of water molecules. In the case of methylated bases, it is also due to the fact that the hydrogen atoms most suitable for the formation of H-bonds have been replaced by a methyl group. A preferred stacked structure is, thus, not due to a hydrophobic interaction between a large bulk of water molecules and the base pair, as believed.
Keywords: konformace nukleové kyseliny; počítačová simulace; Models, Molecular; Hydrogen Bonding; Computer Simulation; vodíková vazba; teplota; Temperature; metylace; voda; molekulární modely; Water; Base Pairing; Nucleic Acid Conformation; Methylation; párování bází